Do we see how they perceive risk? An integrated analysis of risk perception and its effect on workplace safety behavior - Xia, N.; Wang, X.; Griffin, Mark; Wu, C.; Liu, B. (Elsevier Ltd, 2017)
© 2017 Elsevier Ltd While risk perception is a key factor influencing safety behavior, the academia lacks specific attention to the ways that workers perceive risk, and thus little is known about the mechanisms through which different risk perceptions influence safety behavior. Most previous research in the workplace safety domain argues that people tend to perceive risk based on rational formulations of risk criticality. However, individuals’ emotions can be also useful in understanding their perceptions. Therefore, this research employs an integrated analysis concerning the rational and emotional perspectives. Specifically, it was expected that the identified three rational ways of perceiving risk, i.e., perceived probability, severity, and negative utility, would influence the direct emotional risk perception. Furthermore, these four risk perceptions were all expected to positively but differently influence safety behavior. The hypotheses were tested using a sample of 120 construction workers. It was found that all the three rational risk perceptions significantly influenced workers’ direct perception of risk that is mainly based on emotions. Furthermore, safety behavior among workers relied mainly on emotional perception but not rational calculations of risk. This research contributes to workplace safety research by highlighting the importance of integrating the emotional assessment of risk, especially when workers’ risk perception and behavior are concerned. Suggested avenues for improving safety behavior through improvement in risk perception include being aware of the possibility of different ways of perceiving risk, promoting experience sharing and accident simulation, and uncovering risk information.